Are Foreign Institutional Investors Good for Emerging Markets? - Lukas Menkhoff; Michael Frenkel (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2003)
Portfolio flows channeled via institutional investors were the most dynamic capital flows to emerging markets in the 1990s. We use an asymmetric information framework to derive five propositions, to integrate empirical evidence and to suggest policy implications. Opaque information in emerging markets hinders foreign market entrants. Moreover, following financial opening, institutional investors can worsen the position of local investors due to unintentionally creating unbalanced diversification and obscure risks. Finally, foreign institutional investors often amplify investment booms and financial contagion. Therefore, capital account and financial market liberalization needs to be accompanied by careful regulation. – – In den 1990er Jahren waren die Portfolio Flows Institutioneller Investoren die dynamischsten Kapitalströme in die Emerging Markets. In dieser Arbeit leiten wir in einem Rahmen asymmetrischer Information fünf Aussagen ab, stellen diese in einen Zusammenhang mit der existierenden empirischen Literatur und entwickeln daraus entsprechende wirtschaftspolitische Implikationen. Die undurchsichtige Informationslage auf den Emerging Markets behindert vor allem ausländische Marktteilnehmer. Darüber hinaus können Institutionelle Investoren - in Folge finanzwirtschaftlicher Öffnung - die Position lokaler Investoren unabsichtlich durch unausgewogene Diversifikation und undurchsichtige Risiken verschlechtern. Schließlich verstärken Institutionelle Investoren aus dem Ausland oft Investitionsbooms oder finanzielle Ansteckung. Deshalb sollten Kapitalverkehrs- und finanzielle Liberalisierung stets von sorgfältiger Regulierung begleitet werden.
Keywords: F32; O16; 330; Portfolio Flows; Institutional Investors; Emerging Markets; Asymmetric Information; International Capital Flows; Portfolio-Investition; Institutioneller Anleger; Internationale Kapitalmobilität; Asymmetrische Information; Aufstrebende Märkte; Finanzmarktkrise; Welt